Comparison of blood parameters in two genetically different groups of horses for functional longevity in show jumping - Harari, Suzanne; Deretz, Severine; Dumont Saint Priest, Bernard; Richard, Eric; Ricard, Anne (Frontiers in Genetics, 2024)
In order to find early selection criteria to improve the longevity of show jumping horses, a specific protocol was designed. Before entering competition, young horses selected from extreme stallions for longevity were measured for many traits, including blood parameters. Blood samples were taken from 952 horses aged 2 to 4 years old, sired by two groups of stallions: one with unfavorable (U) and the other with favorable (F) extreme estimated breeding values for functional longevity. These breeding values were previously calculated from data on 202,320 horses that participated in show jumping competitions between 1985 and 2022. Functional longevity was defined as time spent in competition, adjusted for the level of performance. The 59 measured parameters included hematology, proteins, cytokines, liver and kidney function, bone and joint health, oxidative stress and endocrinology.Heritability was estimated using a mixed model that accounted for the effect of age, sex, estimated weight, visit (place and date of collection), and animal random additive value with 10,280 horses in pedigree. A Partial Least Square logistic regression was performed to predict the sire group. Age, sex and estimated weight significantly affected 36, 19 and 16 variables, respectively. The visit had a significant effect on all variables. Heritability estimates were high, with 75% higher than 0.20 and 30% higher than 0.50. The most heritable traits included mean corpuscular volume (0.92, se 0.11), mean corpuscular hemoglobin (0.90, se 0.11), white blood cells (0.55, se 0.13), total alkaline phosphatase (0.68, se 0.12) and percentage of γ-globulin (0.57, se 0.12). The logistic regression that predicted the group of sires favorable for longevity identified 16 significant variables. Key findings included: lower mean corpuscular hemoglobin (p-value < 0.001), lower mean corpuscular volume (p-value < 0.001), lower number of white blood cells (p-value < 0.01), higher percentage of intestinal and bone alkaline phosphatase (p-value < 0.01) for a lower total alkaline phosphatase (p-value < 0.01), higher percentage of α2-globulin (p-value < 0.001) and lower percentage of β1-globulin (p-value < 0.01). Blood parameters measured at rest in young horses may be predictive of their genetic value for functional longevity in show jumping.